2005
DOI: 10.1007/s10350-005-0087-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Proximal Colonic Motor Response to Rectal Mechanical and Chemical Stimulation in Obstructed Defecation

Abstract: In obstructed defecation, 1) the normal rectocolonic pathways mediating stimulation-induced proximal colonic propagating pressure waves are nonfunctioning, and. 2) central perception of these rectal stimuli is normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 52 publications
(64 reference statements)
0
23
0
Order By: Relevance
“…In addition to RH, other factors may potentially contribute to constipation, e.g. reflex (viscero‐visceral) inhibition of proximal gut function 10,11 and also a secondary colonic dysmotility (recto‐colonic inhibitory reflexes) 12,13 . In patients with RH and faecal incontinence, it has been proposed that protracted internal anal sphincter relaxation, due to a chronic recto‐anal reflex inhibition secondary to faecal distension/impaction, that is insufficiently compensated for by contraction of the external anal sphincter, 14–16 promotes the involuntary loss of bowel contents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to RH, other factors may potentially contribute to constipation, e.g. reflex (viscero‐visceral) inhibition of proximal gut function 10,11 and also a secondary colonic dysmotility (recto‐colonic inhibitory reflexes) 12,13 . In patients with RH and faecal incontinence, it has been proposed that protracted internal anal sphincter relaxation, due to a chronic recto‐anal reflex inhibition secondary to faecal distension/impaction, that is insufficiently compensated for by contraction of the external anal sphincter, 14–16 promotes the involuntary loss of bowel contents.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in patients with typical symptoms of obstructive defecation, long-time difficulty or incomplete evacuation might also cause overperistalsis and a disorder of the myenteric plexus, thus unavoidably resulting in myopathy or neuropathy of the whole colon. Dinning et al 33,34 found that in patients with severe obstructed defecation without an obvious mechanical cause such as rectocele or levator weakness, abnormal colonic waveforms are found in the distal as well as the proximal colon. 33,34 Total abdominal colectomy with ileorectal anastomosis represents the procedure of choice in patients with pure slow-transit constipation and relieves constipation in most patients.…”
Section: Discussionmentioning
confidence: 98%
“…Dinning et al 33,34 found that in patients with severe obstructed defecation without an obvious mechanical cause such as rectocele or levator weakness, abnormal colonic waveforms are found in the distal as well as the proximal colon. 33,34 Total abdominal colectomy with ileorectal anastomosis represents the procedure of choice in patients with pure slow-transit constipation and relieves constipation in most patients. 35 However, a significant proportion continues to experience other symptoms, particularly urgency and diarrhea.…”
Section: Discussionmentioning
confidence: 98%
“…For example, bile acids enhance colonic motility, in part by stimulating propagating contractions arising in the proximal colon [1, [4][5][6][7]. Increased bile acid exposure also leads to enhanced visceral sensation in response to rectal mechanical stimulation [8]. Bile acids possess detergent effects, increase mucosal permeability and stimulate mucus secretion [1,3].…”
Section: How Might Bile Acids Be Related To Constipation?mentioning
confidence: 99%